What keeps the faith in life, or: What matters - Bayer, Oswald (Vox Scripturae - Revista Teológica Internacional, 2018)
Can there be any faith in theface ofthe temptation? What creates him? The word! Which word? The word of an incredibly great promise. This consists in God's name, which he gives us by giving himse/fto us: Exodus 3.
Keywords: Word (God's Name); Faith; Temptation